2012
DOI: 10.1002/cne.22739
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of tyrosine hydroxylase and serotonergic systems in the regenerating spinal cord of adult zebrafish

Abstract: Monoaminergic innervation of the spinal cord has important modulatory functions for locomotion. Here we performed a quantitative study to determine the plastic changes of tyrosine hydroxylase-positive (TH1(+); mainly dopaminergic), and serotonergic (5-HT(+)) terminals and cells during successful spinal cord regeneration in adult zebrafish. TH1(+) innervation in the spinal cord is derived from the brain. After spinal cord transection, TH1(+) immunoreactivity is completely lost from the caudal spinal cord. Termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
94
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(99 citation statements)
references
References 63 publications
4
94
0
Order By: Relevance
“…Western blot analysis of rat and fish brain extracts, including midshipman, show similar expected bands of 59-63kDa (Adrio et al, 2011;Carrera et al, 2012;Gayoso et al, 2011;Goebrecht et al, 2014;manufacturer's data). This antibody stains the appropriate pattern (i.e., known CA populations of neurons and projection patterns) in all brain regions as previously documented in midshipman and other fish species (Carrera et al, 2012;Goebrecht et al, 2014;Kuscha et al, 2012;McLean and Fetcho, 2004a) and other vertebrates (e.g., Hayes et al, 2011;Nakano et al, 2009). Alternate sections from positively labeled sections incubated without primary or secondary antisera showed a complete absence of labeling.…”
Section: Antibody Characterizationmentioning
confidence: 95%
“…Western blot analysis of rat and fish brain extracts, including midshipman, show similar expected bands of 59-63kDa (Adrio et al, 2011;Carrera et al, 2012;Gayoso et al, 2011;Goebrecht et al, 2014;manufacturer's data). This antibody stains the appropriate pattern (i.e., known CA populations of neurons and projection patterns) in all brain regions as previously documented in midshipman and other fish species (Carrera et al, 2012;Goebrecht et al, 2014;Kuscha et al, 2012;McLean and Fetcho, 2004a) and other vertebrates (e.g., Hayes et al, 2011;Nakano et al, 2009). Alternate sections from positively labeled sections incubated without primary or secondary antisera showed a complete absence of labeling.…”
Section: Antibody Characterizationmentioning
confidence: 95%
“…Recent studies have shown that serotonergic neurons have an impressive regenerative ability aft er spinal cord injury in both zebrafi sh [Kuscha et al, 2011] and lampreys [Cornide-Petronio et al, 2011]. Using a double labeling tract-tracing tech-'Evodevo' is an acronym from the words 'evolution and development' that is used to name the fi eld of life sciences focused on the study of diff erences and similarities in the developmental process of extant species with the aim of understanding how they have evolved from common ancestors.…”
mentioning
confidence: 99%
“…More functional studies are necessary to investigate the role of these molecules as possible inhibitors of the regeneration of dopaminergic axons or as guidance cues for regenerating dopamine axons to be guided to their appropriate target neurons below the site of injury. Previous studies about the role of Slits in the development of the descending dopaminergic projections in zebrafish embryos (see above) and a recent study that has shown that descending dopaminergic fibres partially reinnervate the caudal spinal cord after a complete spinal cord injury in adult zebrafish [29] indicate that adult zebrafish may be an interesting model to study the role of Slits and Robos during the regeneration of dopaminergic axons in the mature CNS.…”
Section: Discussionmentioning
confidence: 99%